Research progress on the correlation between gut microbiota and preeclampsia: microbiome changes, mechanisms and treatments - Zong, Yichi; Wang, Xuguang; Wang, Jun (Frontiers in Cellular and Infection Microbiology, 2023)
Preeclampsia is a specific disease during pregnancy and is a significant factor in the increased mortality in perinatal women. Gut microbiota, an intricate and abundant microbial community in the digestive tract, is crucial for host metabolism, immunity, and nutrient absorption. The onset and progression of preeclampsia are closely correlated with the changes in maternal gut microbiota.Research purpose was to compile the existing bits of present scientific data and to close the gap in the knowledge of changes in gut microbiota in preeclampsia and their association with preeclampsia. We searched studies from two electronic databases (PubMed and Web of Science) included from 2014 to 2023. This review is divided into three parts. In the first part, the author elaborates longitudinal differences of maternal gut microbiota during different gestation periods. In the second part, we discuss that gut microbiota can lead to the occurrence of preeclampsia by systemic immune response, influencing the release of active peptides, short-chain fatty acids, trimethylamine-N-oxide (TMAO) and other metabolites, vascular factors and Microorganism-immune axis. In the third part, we proposed that a high-fiber diet combined with drugs and microecological regulators may be therapeutic in enhancing or preventing the emergence and evolution of preeclampsia, which needs further exploration. Although the pathogenesis of preeclampsia is still nebulous and there is no clear and valid clinical treatment, our study provides new ideas for the pathogenesis, prevention and treatment of preeclampsia.Introduction (Figure 1)Preeclampsia is a specific disease during pregnancy and is a chief factor of increased mortality in perinatal women. It is defined by newly onset hypertension (systolic blood pressure ≥ 140 mmHg